2015
DOI: 10.7554/elife.06541
|View full text |Cite
|
Sign up to set email alerts
|

In vivo dynamics of skeletal muscle Dystrophin in zebrafish embryos revealed by improved FRAP analysis

Abstract: Dystrophin forms an essential link between sarcolemma and cytoskeleton, perturbation of which causes muscular dystrophy. We analysed Dystrophin binding dynamics in vivo for the first time. Within maturing fibres of host zebrafish embryos, our analysis reveals a pool of diffusible Dystrophin and complexes bound at the fibre membrane. Combining modelling, an improved FRAP methodology and direct semi-quantitative analysis of bleaching suggests the existence of two membrane-bound Dystrophin populations with widely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 69 publications
(116 reference statements)
3
16
0
Order By: Relevance
“…This view is in line with the cooperative behavior of dystrophin repeats observed under unfolding conditions when stretched by optical tweezers (36). This compartmentalization may allow dystrophin to recruit protein partners simultaneously while bound to the plasma membrane (37). In particular, the bulkiest molecules, intermediate filaments and F-actin, are recruited by the large R11-17 domain while microtubules are recruited by R20-23 (38) and due to steric hindrance, these interactions could not occur simultaneously with a straight central domain.…”
Section: Discussionsupporting
confidence: 64%
“…This view is in line with the cooperative behavior of dystrophin repeats observed under unfolding conditions when stretched by optical tweezers (36). This compartmentalization may allow dystrophin to recruit protein partners simultaneously while bound to the plasma membrane (37). In particular, the bulkiest molecules, intermediate filaments and F-actin, are recruited by the large R11-17 domain while microtubules are recruited by R20-23 (38) and due to steric hindrance, these interactions could not occur simultaneously with a straight central domain.…”
Section: Discussionsupporting
confidence: 64%
“…Nuclear and dose dependent expression of the transgene was confirmed (Supplementary Figure 1B,C). To test the hypothesis that CBP overexpression improves regeneration, embryos were analysed at 2 dpf, as fibre tips start detaching from somitic borders (Bajanca et al, 2015), and 6 dpf, when regeneration upon damage is underway (Gurevich et al, 2016; Pipalia et al, 2016). While dystrophin -null embryos show characteristic dystrophic muscles from early stages, overexpressing CBP clearly reduced damage not only at later stages but, unexpectedly, also at 2 dpf (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…Phenolthiourea (0.003%) was added to inhibit pigmentation and facilitate muscle analysis. Dystrophic muscles were characterised by abnormal birefringence, supported by observing disruption of the actin reporter pattern when Tg(actc1b:mCherry) pc4 fish were used, and impaired movement (Bajanca et al, 2015; Berger et al, 2012). The absence of Dystrophin expression in rescued embryos was confirmed by immunohistochemistry.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DOI: 10.7554/eLife.06541.007 deliberately avoided. The original data and relevant analysis files for each case are available online (Bajanca et al, 2015) to complement representative examples shown in figures and main data summarised in tables. We conclude that, although there is fibre-specific variation of D, there is no evidence that cytoplasmic Dystrophin either binds cytoskeletal elements or is actively transported towards fibre tips.…”
Section: Dystrophin Diffuses Freely In the Cytoplasmmentioning
confidence: 99%